Exploring the Intersection of Sensory and Chemical Information in the Anti-Predator Response of Daphnia Pulex - Xiong, Ong; Xiong, Nacy (My University, 2014)
The life history and morphological anti-predator response of D. pulex to predators like P. reticulata is usually described as kairomone-mediated responses. To explore if sensory information can modify these responses in D. pulex, we set up an experimental system to test if dim light, which reduces the predation success of visual predators like P. reticulata, will suppress kairomone induced predator-specifc changes.
Color poster with text, images, and figures.
Keywords: Kairomone; Reproduction; Water flea; Daphnia pulex (D. pulex); Posters